INFRASTRUCTURE IMPROVEMENT AND ITS IMPACTS ON THE INDONESIAN ECONOMIC PERFORMANCE - Tony Irawan; Djoni Hartono; Ferry Irawan; Arief Anshory Yusuf (Journal of Indonesian Economy and Business (JIEB), 2012)
Indonesian government shows their big commitment on the improvement of infrastructure which is reflected in some regulations and policies made. It is supported by many empirical evidences that show the importance of infrastructure improvement on the economic performance. This paper developed a Computable General Equilibrium (CGE)model to analyze the impacts of infrastructure on the Indonesian economy by introducing several types of infrastructure and discussing the impacts of it on the poverty level. The results suggest that improvement on any types of infrastructure is expected to increase the economic growth, raise the government revenue, raise the factors’ income and reduce the poverty level. Improvement on the public work of agriculture, land transportation and telecommunication are still being preferable options comparing to others. Interestingly, even though the public work of agriculture is usually located in rural areas, the model suggests that the improvement on this sector will result higher impact on the urban household rather than to the rural household.Keywords: infrastructure, CGE, policy, poverty.